Model Pengelolaan Badan Layanan Umum Daerah Berbasis Teaching Factory Menuju Kemandirian Finansial Sekolah - Setyo, Agus; Mursidi, Mursidi (Jurnal Kebijakan dan Pengembangan Pendidikan, 2020)
Abstract: The purpose of this study is to illustrate the implementation of a teaching service program based on regional public services in 5 vocational high schools in Surabaya. The research methodology used is descriptive qualitative data collection techniques of observation, interviews, and documentation as well as data analysis models of Miles, Huberman, and Saldana; data coding, data presentation, and conclusion drawing. The results of the study explained that the 5 vocational high schools in Surabaya had a teaching factory program that collaborated with the industrial world and produced goods and services that met industry standards. This school has marketed goods and services according to industry standards from the results of student practice so that this school can carry out regional business service agencies from the province of East Java. Proceeds from sales of products and services that have been marketed to the community will be able to increase school income so that the proceeds from the sale can be used to improve the quality and welfare of the school. Local public service agencies based on teaching factories with products produced by students can create school financial independence, without having to always expect help from the government.Keyword: Regional Public Service Board, Teaching Factory, School Financial IndependenceAbstrak : Tujuan penelitian ini untuk menggambarkan pelaksanaan program badan layanan umum daerah berbasis teaching factory di sekolah menengah kejuruan negeri 5 kota Surabaya. Metodelogi penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data pengamatan, wawancara, dan dokumentasi serta analisis data model Miles, Huberman dan Saldana; kodensasi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menjelaskan bahwa sekolah menengah kejuruan negeri 5 kota Surabaya memiliki program teaching factory yang kerjasama dengan dunia industry serta menghasilkan barang dan jasa yang sesuai standar industry. Sekolah ini sudah memasarkan barang dan jasa sesuai standar industry dari hasil praktik siswa sehingga sekolah ini dapat melaksanakan badan layanan usaha daerah dari propinsi Jawa Timur. Hasil penjualan produk dan jasa yang telah dipasarkan ke masyarakat akan dapat menambah pendapatan sekolah, sehingga dari hasil penjualan dapat digunakan untuk meningkatkan mutu dan kesejahteraan sekolah. Badan layanan umum daerah berbasis teaching factory dengan produk yang dihasilkan oleh siswa dapat membuat kemandirian finansial sekolah, tanpa harus selalu mengharapkan bantuan dari pemerintah.Kata Kunci: Badan Layanan Umum Daerah, Teaching Factory, Kemandirian Finansial Sekolah